2022
DOI: 10.1136/thorax-2021-217736
|View full text |Cite
|
Sign up to set email alerts
|

Th2 high and mast cell gene signatures are associated with corticosteroid sensitivity in COPD

Abstract: RationaleSevere asthma and chronic obstructive pulmonary disease (COPD) share common pathophysiological traits such as relative corticosteroid insensitivity. We recently published three transcriptome-associated clusters (TACs) using hierarchical analysis of the sputum transcriptome in asthmatics from the Unbiased Biomarkers for the Prediction of Respiratory Disease Outcomes (U-BIOPRED) cohort comprising one Th2-high inflammatory signature (TAC1) and two Th2-low signatures (TAC2 and TAC3).ObjectiveWe examined w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
2
9
0
Order By: Relevance
“…A Uniform Manifold Approximation and Projection (UMAP) and violin plot show that the majority of IL-33 –expressing cells are resting basal cells and endothelial cells ( Figure 4A and Figure E5A). Although IL1RL1 was found to be expressed mainly in mast cells, mirroring a previous report ( 44 ), it was also present in the endothelial aerocyte capillary cells ( Figure 4B and see Figure E5B), whereas IL1RAP was mainly in monocytes ( see Figure E5C). Based on this finding, we conducted cellular deconvolution to examine the association between smoking status and cellular composition.…”
Section: Resultssupporting
confidence: 88%
“…A Uniform Manifold Approximation and Projection (UMAP) and violin plot show that the majority of IL-33 –expressing cells are resting basal cells and endothelial cells ( Figure 4A and Figure E5A). Although IL1RL1 was found to be expressed mainly in mast cells, mirroring a previous report ( 44 ), it was also present in the endothelial aerocyte capillary cells ( Figure 4B and see Figure E5B), whereas IL1RAP was mainly in monocytes ( see Figure E5C). Based on this finding, we conducted cellular deconvolution to examine the association between smoking status and cellular composition.…”
Section: Resultssupporting
confidence: 88%
“…Transcriptome analysis of bronchial biopsies collected during the GLUCOLD clinical trial reported increased T2-related gene expression in a subset of COPD patients with increased blood and lung eosinophil numbers, which was associated with increased ICS responsiveness [ 106 ]. A subsequent analysis of the GLUCOLD data, using hierarchical clustering of genes previously defined using severe asthma sputum samples, identified subgroups of COPD patients with different transcriptome signatures associated with T2 inflammation, inflammasome activation or mitochondrial activation [ 107 ]. Following ICS intervention, only the T2 signature was supressed.…”
Section: Eosinophils Type 2 Inflammation and Corticosteroid Response ...mentioning
confidence: 99%
“…Furthermore, recent findings by F aiz et al . [ 15 ] through gene expression profiling studies in large airway bronchial biopsies and sputum of moderate-to-severe COPD patients showed an association of MC tryptase and chymase as critical drivers of COPD pathology, with increased suppression seen in the inhaled corticosteroid-treated group of patients. A similar association was also drawn between MC gene expression in the eosinophil high subpopulation of COPD patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%